Gut reaction: impact of systemic diseases on gastrointestinal physiology and drug absorption. Issue 2 (February 2019) - Hatton, Grace B.; Madla, Christine M.; Rabbie, Sarit C.; Basit, Abdul W.
Highlights: Systemic diseases unrelated to the GI tract can affect physiology and function. GI abnormalities can affect the bioavailability of orally administered drugs. Intestinal microbial dysbiosis is prevalent across all disease indications. Onset of cystic fibrosis, diabetes and pain can alter drug pharmacokinetics. Aetiology of Parkinson's disease can originate in the gut. Abstract : It was in 400 BC that Hippocrates reportedly stated that "death sits in the colon". The growth in our knowledge of the intestinal microbiome, the gut–brain axis and their function and imbalance has distinctly uncovered the complex relationship between the gut to disease predisposition and development, heralding the problem and the solution to disease pathology. Human studies of new drug molecules are typically performed in healthy volunteers and their specific disease indication. Approved drugs, however, are used by patients with diverse disease backgrounds. Here, we review the current literature of the gastrointestinal tract reacting to systemic disease pathology that elicits physiological and functional changes that consequently affect oral drug product performance. Teaser: Systemic diseases where foci are initially unrelated to the GI tract do in fact alter GI physiology and function. This ultimately affects the bioavailability of orally administered drugs.